Analisis Konsistensi Kinerja Reksa Dana Saham di Indonesia dan Kemampuan Manajer Investasi dalam Hal Market Timing serta Stock Selection - , FADHILAH RAHMATINA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aimed to evaluate the performance, consistency of mutual funds in Indonesia by doing some different measurements and also to analyze the ability of stock selection and market timing of investment managers. This study used 32 mutual funds which listed in BAPEPAM period 2009-2013. The methode used to analyze the performance of mutual funds was risk adjusted performance. This study evaluated the performance consistency of mutual funds useing Kendall-W. Treynor-Mazuy and Henriksson-Merton model was used to test timing and stock selection ability of mutual fund managers. The results of this study indicate that the performance of 28 % mutual funds in Indonesia during 2009 till 2013 was outperform comparing the benchmark (IHSG). Kendall 's W Test results had value of Kendall-W (0.334) that lower than 0,50. It showed there was little consistency on performance of mutual fund shares in Indonesian by using Sharpe, Treynor and Jensen index measurement. The results of the Treynor-Mazuy and Henriksson- Merton methode showed that there were 10 mutual funds that have Î³ significant positive and 3 mutual funds that have Î± significant positive. By doing mutual funds individually analysis, there were investment managers who had ability of market timming and stock selection on equity funds in Indonesia.